Science as rhetoric in media discourses on climate change - Ramos, Rui Lima (2008)
This article aims to analyse and describe the organization of reported speech in a corpus of Portuguese newspaper articles, as well as the way such texts function in terms of rhetoric and argumentation. The focus is on media discourse on the science(s) of climate change, including reports on new studies, publications, expert testimonies, etc. In Portugal, news discourses on climate change have a strong interdiscursive relation with scientific discourse and tend to present science as an authoritative source of reliable knowledge. This reliance on scientific discourse is associated with a media strategy of persuasion of the audience, the effectiveness of which depends on the representations of validity of scientific knowledge. By evoking voices from the science community, the journalist can both project an image of neutrality and legitimise her/his discourse. This is instrumental for the success of her/his illocutionary goals, for the acceptance of her/his speech and even for the public sanction of a given discourse on the environment